Keabsahan Jenis Hewan Kurban Menurut Perspektif Imam Syāfi’ī dan Imam Ibnu Ḥazm - Ahmad Syaripudin; Sirajuddin Sirajuddin; Sudarwan Sudarwan (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2023)
This study aims to determine the validity of the types of sacrificial animals from the perspective of Imam Syāfi’ī Imam and Imam Ibnu Ḥazm. The issues raised in this research are; the perspective of Imam Syāfi’ī and Imam Ibnu Ḥazm on the validity of the types of sacrificial animals and their argumentative basis. This type of research is descriptive qualitative using a literature review method focusing on manuscript studies, with a comparative study approach method. The results of this study are as follows: First, Imam Syāfi’ī's perspective regarding the validity of the types of sacrificial animals that are legally used as sacrificial animals is only Bahīmah al-'An'ām as for animals that are other than illegal as sacrificial animals. As for the perspective of Imam Ibnu Ḥazm regarding the validity of sacrificial animals that are legally used as sacrificial animals, they are any type of animal whose meat is halal, whether it has four legs or two legs. Second, Imam Syāfi’ī and Imam Ibnu Ḥazm have the same perspective that Bahīmah al-'An'ām is legally used as a sacrificial animal. However, Imam Syāfi’ī and Imam Ibn Ḥazm have different perspectives other than that Bahīmah al-'An'ām is legal or illegal to be used as a sacrificial animal; the main argumentative foundation of Imam Syāfi’ī is. Q.S. Al-Hajj/22: 34. Meanwhile, the argumentative basis of Imam Ibn Ḥazm's argument was narrated from Abdullah bin Abbas and Bilal bin Rabbah.